Análise da configuração de SAMU utilizando modelo hipercubo com prioridade na fila e múltiplas alternativas de localização de ambulâncias - Souza, Regiane Máximo de (Universidade Federal de São Carlos, 2010)
In some emergency medical systems the service demand is high due to the treatment of patients in the range severe to mild, which increases the utilization level of the servers. In these systems, may be queues formation and so the need to explicitly consider priority in care is extremely important. In this study we extend the hypercube model to deal with this situation never explored in the literature. Besides that, the geographical and temporal demand of SAMU can change throughout the day due to their random nature. The goals of this study are: (a) to extend the model in order to consider hypercube priority queue, which as far as we know has never been done in the literature and (b) to propose an approach for multiple configurations of ambulances´ localization, exploring important variations in demand and service throughout the day. In this work, in order to verify the feasibility and applicability of this approach, we conducted a case study at Ribeirão Preto´s SAMU (SAMU-RP) that, apart from urgent care and emergency operates removing patients (transporting patients between hospitals, from hospital to home and vice versa). Besides the original configuration of SAMU-RP, we analyzed five alternatives scenarios to examine three important issues: the impact of the removals, the impact of increased demand at the busiest periods and the possibility of multiple configurations for the localization of ambulances in the three analyzed periods in important performance measures of the system, like: workloads, travel times, response times for users, etc. The results show that the hypercube model with priority in the queue can be used to analyze systems like SAMU-RP and it allows sufficiently rapid and accurate evaluation of the performance, of the system in several scenarios.
Keywords: Pesquisa operacional; Processos estocásticos (Aplicações); Teoria das filas; Modelo hipercubo; Atendimento médico - emergencial; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL::PROCESSOS ESTOCASTICOS E TEORIAS DA FILAS